Phylogenetic Relationships of Rhizobia Based on Citrate Synthase Gene Sequences - Hernández Lucas, Ismael (2004)
Partial nucleotide sequences of the citrate synthase (gltA) gene from different rhizobia genera were determined. Tree topologies based on this housekeeping gene were similar to that obtained using 16S rRNA sequences. However gltA appeared to be more reliable at determining phylogenetic relationships of closely related taxa. We propose gltA sequences as an additional tool to be used in molecular phylogenetic studies.